Hutanomics: Digital Economy Innovation for Strengthening Forestry Economic Resource Management - Budiman Budiman (Universitas Dharma Wacana, 2022)
This research trying to explains the management of the nation's economic development based on preserving the environment, which is the forest. This is because economic development has always been identified with environmental damage, including deforestation. As one of the countries with the largest tropical rainforest globally, Indonesia is automatically one of the focuses on its economic development is utilizing existing forestry resources. This causes a massive deforestation process, so the international community pressures Indonesia by accusing Indonesia of being one of the world's countries that cause climate change. Therefore, currently, the Government of Indonesia has established a Green Economy Development Program to overcome the problem of climate change caused by economic activities. The idea of Green Economic Development is essential to discuss because of the nation's priority for strong economic growth and sustainable development. One form of green economic development is to introduce the hutanomics concept, a concept of economic development management that is harmonized and based on the interests of forests and nature, which the author has adopted as the theme of this research. With a qualitative approach, the descriptive method, the researcher explains the management of the nation's economic development based on preserving the environment, which is the forest. Research findings show that economic development does not always have to come at the expense of the environment like deforestation. One of the concepts introduced is Hutanomics (Forest Economic), a management concept of economic development by aligning economic interests with the interests of forests and nature. Environmental impact analysis is critical to Hutanomics because it involves the claims of nature and the necessity of a collaboration between the government, the corporate world, and the community, each with their own functions